Effect of plyometric training on sport performance in adolescent overhead athletes: A systematic review - Eraslan, L.; Castelein, B.; Spanhove, V.; Orhan, C.; Duzgun, I.; Cools, A. (Sports Health: A Multidisciplinary Approach, 2021)
Context: Plyometric training has been shown to be beneficial in adolescent overhead athletes. However, existing research on the effects of plyometrics on sport performance has been limited.